Association between dietary intake of fatty acids and colorectal cancer, a case-control study - Shekari, Soheila; Fathi, Soroor; Roumi, Zahra; Akbari, Mohammad Esmail; Tajadod, Shirin; Afsharfar, Maryam; Hasanpour Ardekanizadeh, Naeemeh; Bourbour, Fatemeh; Keshavarz, Seyed Ali; Sotoudeh, Mahtab; Gholamalizadeh, Maryam; Nemat Gorgani, Shiva; et al. (Frontiers in Nutrition, 2022)
Background: The association of dietary fat and colorectal cancer (CRC) was frequently reported. However, few studies assessed the different effects of different types of dietary fats on CRC. This study aimed to investigate the association between intakes of different types of dietary fatty acids with colorectal cancer risk. Methods: This case-control study was conducted on 480 participants including 160 CRC cases and 320 healthy controls in Firoozgar Hospital, Tehran, Iran. The intake of dietary fatty acids of the participants was assessed using a semi quantitative food frequency questionnaire (FFQ). Results: The mean intake of cholesterol (273.07±53.63 vs. 254.17±61.12, P=0.001), PUFA (16.54±4.20 vs. 15.41±4.44, P=0.012), and calorie (2568.76± 404.48 VS 2493.38 ±176.03, P=0.006) was higher than and the mean intake of oleic acid (5.59±3.17 vs. 8.21±5.46) and linoleic acid (6.03±3.44 vs. 7.02±4.08, P=0.01) was lower in the case group compared to the control group. An inverse association was found between colorectal cancer (CRC) and dietary intake of oleic acid (OR: 0.85, CI 95% 0.80-0.90, P=0.001), linoleic acid (OR: 0.85, CI 95% 0.78- 0.93, P=0.001), and α-linolenic acid (OR: 0.75, CI 95% 0.57- 0.98, P=0.04), and. The association remained significant after adjusting for age and sex, sleep, smoking, and alcohol consumption, and BMI. Conclusions: The results of this study support a protective effect of oleic acid, linoleic acid, and α-linolenic acid against CRC. Higher intake of LA and ALA was associated with reduced risk of colorectal cancer. Further longitudinal studies are warranted to confirm these results.